Design optimization and material selection of automotive bushing arms using FEA under acidic exposure - Ana Nur Oktaviani; Dafit Feriyanto; Haftirman Haftirman; Supaat Zakaria; Dedik Romahadi; Hadi Pranoto; SS Abdulmalik (Jurnal Polimesin, 2026)
Bushing arms are critical automotive components that function as vibration dampers and load absorbers. The problem is that the bushing arm often fails due to several factors, including the use of inappropriate materials, poor road quality, lack of routine maintenance, and external factors such as extreme temperatures, exposure to corrosion, and excessive pressure. This study aims to optimize bushing arm design and material selection to improve durability and vibration-damping performance under acidic exposure conditions. Two rubber materials, Natural Rubber (NR) and Ethylene-Propylene Diene Monomer (EPDM), were evaluated for MPV-type vehicle bushing arms. Three design variations were developed and analyzed using hyperelastic Finite Element Analysis (FEA) to assess stress distribution, strain, deformation, and safety factor. The rubber specimens were fabricated by hot pressing at 180°C and 7 MPa, followed by immersion in 15% phosphoric acid at 65°C to evaluate chemical degradation. Mechanical characterization included tensile testing (ASTM D412), Shore hardness testing, and microstructural observation. The results showed that acid immersion reduced tensile strength by 20.44% for NR and 23.80% for EPDM, while elongation decreased by 38.3% and 17.43%, respectively. Hardness decreased by 19.2% for NR and 4.81% for EPDM. FEA results indicated that design C achieved the lowest deformation, reducing it by 51%, while design B reduced shear stress and von Mises stress by up to 70%. Based on the combined mechanical and simulation results, design B with NR material was selected as the preferred configuration.